Rehabilitation of biceps tendon disorders in athletes - Ryu, J. H. J.; Pedowitz, R. A. (Clinics in Sports Medicine, 2010)
The diagnosis and management of an active patient with biceps disease can be challenging for the treating physician. A careful review of the function, anatomy, and pathology of biceps in conjunction with a thorough, knowledgeable history and physical examination can yield a working diagnosis in this challenging patient population. The physician must also be aware of the physiology of postsurgical repair and advocate appropriate rehabilitation activities that correlate with the timeline of secure tissue healing. This article focuses on nonsurgical rehabilitation and postoperative rehabilitation of biceps tendon injuries.